Wacana Kebijakan Pengampunan Koruptor dalam Bingkai Media Online Tempo.co dan Metrotvnews.com Periode 19-31 Desember 2024 - Mahisa Gesty Anggasani; Hanna Nurhaqiqi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
As the country’s top leader, it is common that Prabowo has become a central figure in the public eye. Recently, one of Prabowo’s statements has sparked public discussion and is considered controversial. The statement in question is his expression of willingness to forgive corruptors, provided they return the stolen assets. Many people have linked the discourse with the image of fake heroism that has been associated with Prabowo since the beginning of his presidency. The construction of this image is influenced, in part, by the role of the media. Tempo.co and Metrotvnews.com are among the online news portals that reported on the discourse surrounding the amnesty policy for corruptors. This research employs Robert N. Entman’s framing analysis model to examine how Tempo.co and Metrotvnews.com frame the discourse. The research object selected consisted of news articles on the discourse of an amnesty policy for corruptors, published between 19 and 31 December 2024 with 6 articles from Tempo.co and 5 articles of Metrotvnews.com. Tempo.co tends to citicize Prabowo’s statement and does not support the realization of the proposed policy of granting clemency corruptors. Meanwhile Metrotvnews.com presents the policy discourse more favorably, potraying it as an effective approach to recovering state assets.